Synthesis and electrochemistry of tetrakis(7-coumarinthio-4-methyl)-phthalocyanines, and preparation of their cinnamic acid and sodium cinnamate derivatives - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Novel water soluble free-base, Zn(II) and Co(II) metallo phthalocyanines with four cinnamic acid moieties were prepared from the corresponding tetrakis(7-coumarinthio-4-methyl)-phthalocyanine by the lactone ring opening reaction. The new compounds were purified and characterized by elemental analysis, H-1 NMR, Maldi-TOF, FT-IR and UV-Vis spectral data. Cyclic and differential pulse voltammetry and in situ spectroelectrochemistry of the 2,9,16,23-tetrakis(7-coumarinthio-4-methyl) substituted free-base 1a, Zn(II) 1b and Co(II) 1c phthalocyanines, employed as the starting compounds have been studied. This allowed us not only to identify metal- and phthalocyanine ring-based redox processes of the complexes, but also the effect of aggregation on these processes. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanines; Cinnamic acid; Coumarin (2H-1-benzopyran-2-one); Cobalt; Zinc; Spectroelectrochemistry; PHOTOCHEMICAL FORMATION; ZINC PHTHALOCYANINE; SUBSTITUTED COBALT; PECHMANN REACTION; METALLOPHTHALOCYANINES; COMPLEXES; IRON